Tuning Mixed‐Valent Eu2+/Eu3+ in Strontium Formate Frameworks for Multichannel Photoluminescence. Issue 32 (30th June 2016) - Liu, Wei; Liu, Lijia; Wang, Yanlong; Chen, Lanhua; McLeod, John A.; Yang, Linju; Zhao, Jia; Liu, Zhiyong; Diwu, Juan; Chai, Zhifang; Albrecht‐Schmitt, Thomas E.; Liu, Guokui; et al.
Abstract: Cooperative performance of mixed‐valent Eu 2+ /Eu 3+ in single‐compound phosphors offers significant advantages in color rendering and luminescence efficiency, but their synthesis is challenging because of Eu 2+ oxidation. Using the tunable nature of the metal‐ion nodes in metal–organic frameworks (MOFs), we present an in situ reduction and crystallization route for preparing MOFs and doping Eu 2+ /Eu 3+ with a controlled ratio. These materials exhibit rich photoluminescence, including intrinsic‐ and sensitized‐emissions of Eu 2+ and Eu 3+, and long‐lived luminescence from charge transfer. Color rendering can be easily achieved by fine‐tuning the valence states of Eu. A linear relation between temperature and the intensity ratio of Eu 2+ /Eu 3+ emissions provides outstanding properties for applications as self‐calibrated luminescent thermometers with a wide working temperature range. Further incorporation of Tb 3+ into the MOFs results in white light, utilizing all Eu 2+, Tb 3+, and Eu 3+ emissions in a single crystalline lattice. Abstract : Trapping gives color : The first simultaneous trapping of mixed‐valent Eu 2+ /Eu 3+ in a metal–organic framework leads to unprecedentedly rich photoluminescence properties. These properties include fine luminescence color rendering from red to blue achieved by the adjustment of Eu valence states, long‐lived green emission stemming from intervalence charge transfer, and an extremely wide working temperature range as a luminescent thermometer.